Health professions education as a national industry framing of controversies in nursing education and migration in the Philippines - Masselink, Leah E. (ProQuest LLC, 2009)
During the past few decades, the nursing workforce has been in crisis in the United States and around the world. An aging work force and high rates of burnout and turnover has caused a global shortage of nurses of unprecedented proportions. Many health care organizations in developed countries have resorted to recruiting nurses from other countries in order to maintain acceptable staffing levels. The Philippines is the largest source country for foreign-trained nurses in the United States and an important supplier of nurses worldwide. Exporting nurses has been a long-standing economic strategy for the Philippine government, despite the fact that the Philippines' domestic health system is weak and existing supplies of health workers are poorly distributed. The Philippine nursing profession is now aimed more at global markets than supplying domestic needs. Despite longstanding awareness of the "internationalization" of the Philippine nursing profession, the logics and thought processes that underlie the phenomenon are poorly understood. This study aims to uncover the discursive construction of nurse migration by various stakeholders ("migrant institutions") through case studies of two recent controversies in nursing education and migration in the Philippines: a leakage of answers on the nursing licensure exam and the inclusion of nurses in a trade agreement with Japan. It employs frame analysis of the newspaper coverage of the two controversies and key informant interviews of government, health sector, education and professional organization representatives to examine how the priorities of economic development, migrants' rights and professional development of nurses are debated in the Philippines. The study finds broad support for interpretations of the controversies that position Filipino nurses as export products on the global market, which are linked to their professional development and often minimize concerns about their rights as migrants. --Abstract.